Strengthening the Faith and Motivation of Students to Learn through Religious Guidance at the Al-Kautsar Punggur Islamic Boarding School, Batam City - Parnawi , Afi; Siti Khotijah, Ellis; Hikmah, Mariatul (IMPACTS: International Journal of Empowerment and Community Services, 2025)
Purpose: This community service aims to strengthen the faith and learning motivation of students through religious mentoring activities at Al-Kautsar Islamic Boarding School, Punggur, Batam City. This activity is needed because religious mentoring plays an important role in shaping students’ character, strengthening faith, and integrating worship values with learning activities in daily life. Methods:The community service activities were conducted through intensive and sustainable religious mentoring carried out by kiai, ustadz, and asatidz. The mentoring process was implemented through religious guidance, worship practices, motivational activities, and learning approaches based on the values of the Qur’an and Sunnah. Result and Discussions: The results showed that the mentoring activities succeeded in increasing students’ intrinsic motivation and strengthening their faith. Students became more enthusiastic in learning because they viewed the learning process as part of worship and good deeds. In addition, the Islamic boarding school environment, structured religious programs, and the culture of mutual reminders contributed positively to the development of discipline, noble character, and continuous learning habits among students. Conclusion: Religious mentoring at Al-Kautsar Islamic Boarding School has proven to be an effective strategy for developing students with strong faith, good character, and high motivation to learn. Continuous mentoring programs and periodic evaluations are recommended to improve the sustainability and effectiveness of the activities in the future.